Long-term effects of the testicular torsion on the spermatogenesis of the contralateral testis and the preventive value of the twisted testis orchiepididymectomy - Lorenzini,Fernando (2012)
PURPOSE: To determine whether the testicular torsion causes long-term effects on the spermatogenesis of the contralateral testis, and whether the orchiepididymectomy of the twisted testis could prevent them, using specific spermatogenesis parameters to elucidate the conflicting results in the literature. METHODS: Seventy-four pubertal male Wistar rats were randomly selected. The experimental group consisted of 40 rats, divided into four subgroups, submitted to 1.080 degrees counterclockwise left testicular torsion and its scrotal fixation at the beginning of the experiment, and left orchiepididymectomy at one, five, ten and 90 days, respectively. The control group consisted of 24 rats, divided into four sham operation control subgroups. An additional control subgroup consisted of the ten remaining rats, submitted only to the left orchiepididymectomy at the beginning. At 90 days, the contralateral testes of the experimental and control subgroups were collected for the evaluation of their spermatogenesis parameters: testicular weight, seminiferous tubular diameter, Johnsen score and differential counting of the germ cells. RESULTS: No statistically significant differences were observed among the experimental and control subgroups for all of the spermatogenesis parameters of the contralateral testes. CONCLUSIONS: Testicular torsion does not cause long-term effects on the spermatogenesis of the contralateral testis in pubertal rats, and the orchiepididymectomy of the twisted testis is not necessary for preventive purposes for the contralateral spermatogenesis.